Burnout, coping and resilience of the cancer care workforce during the SARS-CoV-2: A multinational cross-sectional study - Cloconi, Constantina; Economou, Mary; Charalambous, Andreas (My University, 2023)
Over the past year, the SARS-CoV-2 pandemic has significantly increased the demand placed on health care professionals around the world. The already complex cancer care has been complicated further by the restructuring of services (e.g., working processes, treatment allocation). This study was designed to explore the level of burnout, coping and resilience of the cancer care workforce during SARS-CoV-2.
Keywords: Burnout; Cancer; Coping; Healthcare professionals; Oncology; Resilience; SARS-CoV-2